Can Dynamic Breaks improve the intensity of Physical Education classes? A teaching experience of a pre-service teacher as a practitioner researcher - Daniel Castro Vieira; Fernando Manuel Paulo Cunha; Ana Mafalda Coelho da Silva; Paula Maria Fazendeiro Batista (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2023)
Youth Physical Activity promotion has been identified as a global health priority by the World Health Organization. School is one of the places where it is possible to literate youth about active and healthy life. Physical Education classes are a cornerstone to promote daily physical activity, but most of these classes don’t meet the recommendations of spending at least 50% of the time in moderate-to-vigorous physical activity. Sports such as volleyball, gymnastics and others seem to produce lower-intensity classes than basketball, football and handball. This teaching experience aims to explore the contribution of introducing dynamic breaks in Physical Education classes according to content (volleyball and gymnastics) and gender on time spent in moderate-to-vigorous physical activity. Twenty students, aged between 16 and 18 years old, participated in eight monitored Physical Education classes. In the first four, data was collected without dynamic breaks, introducing them in the four following classes. The students wore POLAR heart rate monitors to measure their moderate-to-vigorous physical activity time. All data was analysed using the Wilcoxon test. Dynamic breaks significantly increased students time spent in moderate-to-vigorous physical activity in both contents, especially in girls. Dynamic breaks can be a valuable strategy to increase the Physical Education classes’ intensity.